2019
DOI: 10.1016/j.ijscr.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal, retroperitoneal, and subcutaneous emphysema due to sigmoid colon penetration: A case report and literature review

Abstract: Highlights Massive mediastinal emphysema is rare signs of colon perforation. The diagnosis may be delayed due to the absence of peritoneal irritation. Laparotomy should be considered in case of colonic penetration with the mediastinum emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Several case reports were reviewed by Muronoi et al 12 In these cases, retroperitoneal emphysema was also reported, while, in the current case, unlike previous reported cases, no gas was seen in the retro-or intraperitoneal spaces. It seems that because the fistula created between the intestine and the abdominal wall had no leakage to the abdominal space, no retro-or intraperitoneal emphysema occurred.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Several case reports were reviewed by Muronoi et al 12 In these cases, retroperitoneal emphysema was also reported, while, in the current case, unlike previous reported cases, no gas was seen in the retro-or intraperitoneal spaces. It seems that because the fistula created between the intestine and the abdominal wall had no leakage to the abdominal space, no retro-or intraperitoneal emphysema occurred.…”
Section: Discussionmentioning
confidence: 46%
“…None of the cases reviewed by Oetting et al 14 and Muronoi et al 12 showed signs of infection and generalized peritonitis before the onset of the occurrence of emphysema. Similar to previous case reports, in the present case, there was no evidence of infection and generalized peritonitis during preoperative examinations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Since 2017, there have been few reports detailing pathological colonic perforation, with only three describing extraperitoneal diverticular perforation [7,8]. Only one case reported pneumothorax and three extraperitoneal perforation after diagnostic colonoscopy.…”
Section: Introductionmentioning
confidence: 99%